A criação de unidades de conservação no Espírito Santo entre 1940 e 2000: contextualização, conflitos e redes de interesse na apropriação social do meio ambiente - Santos, Leonardo Bis dos (2016)
Discussions about the environment are part of the day. They come up as subject in the most variable circles, given its relevance to the continuous material reproduction of the society. Products with green seals certifications and political parties whose main concern is the environmental cause is part of people's lives daily. But how have this agenda been built in recent history? Following this thought, the present thesis, initiating from the case study of the state of Espírito Santo (Brazil) between the years 1940 and 2000, aims to contribute with data and information source. Theoretically, this study consists of the dialog between Political History and Environmental History, applying concepts of renowned authors like Pierre Bourdieu. Empirically, the objective was to tabulate the creation of protected areas or conservation units, which can be seen as government actions in order to conserve nature. Given the time range the study covered, it could be noticed the origin, organization and consolidation of the government operation, showing the development of the actions, single and/or collective, about the different forms of use of the natural resources, sometimes visible in the economy, politics and/or sociocultural habits. That way, it becomes very clear that in the period of arising of this new politics, given the absence of organized social movements, the political capital of its defensors was imperative. By the time in which the progress of the democracy in Brazil and the international context of questioning the models of wealth accumulation and the exhaustion of the natural resources in the planet, the envinronmental schedule in the state of Espírito Santo (Brazil) begins to mobilize more and more agents to its cause. The individual political capital slowly gives place to the symbolic capital deriving out of the social mobilization. This change, in the course of six decades, is notable in the process of definition of public agendas. The total of the material was analysed according to main principles of network and social conflict, on the constant and contradictory movement of interrelationship.